APLIKASI PELACAK KORUPSI ANTAR LINGKUNGAN SEKITAR - Afdal Rahman Jonedi; Randi Febriansyah; Sofyan Mufti Prasetiyo (BULLET : Jurnal Multidisiplin Ilmu, 2022)
An application is a system project in which a system creates a domain that will later be used as a tool for certain needs. Transactions are a structure of the exchange system or as payment in the form of goods and means of payment. Transactions become a center or tool that makes it easier for someone to make payments such as sending money, in this digital era transactions are made into digital money payments or called online payments. Corruption is a Corruption derived from the Latin word Corruptus and Corruption, meaning bad, bejad, deviating from chastity, insulting words, or slandering. In the Black Law Dictionary in the KPK Corruption Crime module, Corruption is an act carried out with the intention of obtaining some benefits that are contrary to official duties and other truths "something of an act of an official or belief of a person which by breaking the law and full of mistakes uses a number of benefits for himself or others that are contrary to other duties and truths.